The Impact of Competitive Relations to Regional Real Estate Markets in Terms of Institutional Support (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In the article the research of institutional support regional real estate markets in a competitive and determined their subjects according to the criteria of distribution are analyzed factors influence the institutional support of the regional real estate markets, the ways of their regulation. This institutional support played an important role in the existence of regional real estate markets. Institutional support for regional real estate markets is structuring its economic processes, the relationship between them is within certain institutions guaranteeing order and subordination of the whole system of market relations. The very interaction between institutional segments is needed by means of coordination, harmonization and streamlining of joint action. This process is characterized by the special procedures and real estate transactions that fall within the scope of the special institutions and organized institutional entities.
Keywords: real estate market, institutions, institutional infrastructure, neoinstytutsionalizm, investors, realtors, developers